A low-power, low-cost, chamber-based CO2 sensor - Saccardi, Brian E.; Dere, Ashlee L.; Goodwell, Allison E.; Druhan, Jennifer; Welp, Lisa R.; Blair, Neal E.; Bauer, Erin; Haken, James; Jimenez-Castaneda, Martha E.; Filley, Timothy; Frantal, Ian; Kumar, Praveen (Frontiers in Water, 2025)
Soil CO2 fluxes are a key component of the terrestrial carbon cycle. However, these fluxes are notoriously expensive to measure, especially in remote and understudied regions. This is primarily due to the cost of methods currently in use to measure soil CO2 fluxes. To address this gap, we developed and tested a low-cost, lightweight, and portable CO₂ flux chamber designed for use in remote environments. The chambers we developed are built from primarily open source and off-the-shelf components that use minimum power and are designed to be easy to construct and use. We evaluated the sensors’ performance through error analysis and tested them in the field at agricultural and prairie sites in Illinois and Nebraska USA. We use field data to produce a partial soil CO2 budget using the chamber flux estimates and production estimates from a gradient-based method. Overall, the results show that chamber size and sampling frequency can be used to reduce measurement error. Additionally, our results fall within the observed ranges for prairie CO2 fluxes in the literature. The simplicity, affordability, and ease of construction of our design make it a valuable tool for expanding soil carbon flux monitoring networks, facilitating education, and improving our understanding of ecosystem carbon budgets.